Pelatihan Guru PAUD Menggunakan Komik Digital dalam Meningkatkan Kesiapsiagaan Bencana Gunung Merapi - Hanifah, Siti; Kurniati, Euis (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This dedication aims to train early childhood education (PAUD) teachers using digital comics as a learning media to enhance disaster preparedness for Mount Merapi among young children. In the face of the threats faced by the community around Mount Merapi in Dusun Nganggring, Sleman, Special Region of Yogyakarta, disaster preparedness education becomes crucial, especially for children vulnerable to disaster impacts. This dedication employs Participation Action Research (PAR). Data collection techniques include interviews and training. The research steps involve identifying community issues through interviews, planning and designing the dedication program, implementing the dedication program through PAUD teacher training, and presenting research findings. The training method involves using specially designed digital comics tailored to the understanding of young children and the characteristics of Mount Merapi disasters. The results of the dedication show that PAUD teacher training in Dusun Nganggring, Sleman using digital comics can create interactive learning media for disaster preparedness steps, strengthen children's awareness of disaster risks, and develop responsive skills when faced with emergency situations. The implications of these findings underscore the importance of integrating engaging and relevant digital media in disaster preparedness education for young children, highlighting the pivotal role of PAUD teachers in effectively delivering information and motivating learners.